2017
DOI: 10.1111/apha.12897
|View full text |Cite
|
Sign up to set email alerts
|

Temporal overexpression of SIRT1 in skeletal muscle of adult mice does not improve insulin sensitivity or markers of mitochondrial biogenesis

Abstract: Aims Activation of the NAD+ dependent protein deacetylase SIRT1 has been proposed as a therapeutic strategy to treat mitochondrial dysfunction and insulin resistance in skeletal muscle. However, life-long overexpression of SIRT1 in skeletal muscle does not improve parameters of mitochondrial function and insulin sensitivity. In this study we investigated whether temporal overexpression of SIRT1 in muscle of adult mice would affect skeletal muscle mitochondrial function and insulin sensitivity. Methods To cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…Correspondingly, muscle‐specific overexpression of SIRT1 was recently shown not to prevent glucose intolerance and impairment in insulin‐stimulated glucose uptake in mice after 12 wk of 60 E% HFD (36). Further, lean mice with either a conventional, germ line (37), or an acute inducible (38) skeletal muscle‐specific overexpression of SIRT1 did not enhance skeletal muscle insulin‐stimulated glucose uptake. Positive effects of SIRT1 activation on insulin‐stimulated glucose uptake with small molecule activators (2, 3) or via increasing NAD + availability (46) in insulin‐resistant rodents may likely be explained by effects of SIRT1 in other tissues than skeletal muscle.…”
Section: Discussionmentioning
confidence: 93%
“…Correspondingly, muscle‐specific overexpression of SIRT1 was recently shown not to prevent glucose intolerance and impairment in insulin‐stimulated glucose uptake in mice after 12 wk of 60 E% HFD (36). Further, lean mice with either a conventional, germ line (37), or an acute inducible (38) skeletal muscle‐specific overexpression of SIRT1 did not enhance skeletal muscle insulin‐stimulated glucose uptake. Positive effects of SIRT1 activation on insulin‐stimulated glucose uptake with small molecule activators (2, 3) or via increasing NAD + availability (46) in insulin‐resistant rodents may likely be explained by effects of SIRT1 in other tissues than skeletal muscle.…”
Section: Discussionmentioning
confidence: 93%
“…While lifelong overexpression of SIRT1 in skeletal muscle did not improve insulin resistance, it was suggested that a temporal overexpression of SIRT1 in muscle of adult mice would affect insulin sensitivity of skeletal muscle. However, this hypothesis could not be confirmed …”
mentioning
confidence: 83%
“…Another proposed strategy to treat insulin resistance in skeletal muscle and thereby diabetes is the activation of the NAD + ‐dependent protein deacetylase sirtuin 1 (SIRT1) . SIRT1 plays a role in changes in cellular energy status to adaptive changes in insulin signalling.…”
mentioning
confidence: 99%
See 2 more Smart Citations